Finance professionalism in the 21st century : are finance undergraduates today ready to be finance professionals? - Lee, Hui Xin. (2013)
Financial frauds and scandals have thrown the finance profession into the spotlight as practitioners in the industry come under pressure from severe public criticisms. In view of the high public expectations placed on the degree of professionalism among finance professionals, this study seeks to provide insights into finance professionalism in today’s context. “Dimensions of Professionalism”, coined by Richard H. Hall in 1968, was utilized as a frame for reference in this study to uncover the understanding of professionalism and to explore the degree of professionalism among finance undergraduates. Correlation analysis was employed to examine the extent to which these undergraduates’ degree of professionalism is related to their views on the financial frauds and scandals and to initiatives by regulatory parties to strengthen professionalism in the finance industry. Data showed that current finance undergraduates may still be far from the ideals of professionalism as practiced by more traditional professions like accounting, medicine or law. Specifically, the data showed that majority of the finance undergraduates considered professional knowledge, instead of attitudes, to be important in a professional. Clearly, more has to be done to raise the degree of professionalism among them. Possible initiatives that educational institutions may take to assist finance undergraduates in their professional development are also examined. Lastly, implications and suggestions for future research are discussed.